12 min/week of high-intensity interval training reduces aortic reservoir pressure in individuals with metabolic syndrome: a randomized trial. Issue 10 (October 2016) - Ramos, Joyce S.; Dalleck, Lance C.; Ramos, Maximiano V.; Borrani, Fabio; Roberts, Llion; Gomersall, Sjaan; Beetham, Kassia S.; Dias, Katrin A.; Keating, Shelley E.; Fassett, Robert G.; Sharman, James E.; Coombes, Jeff S.
Abstract : Objective: Decreased aortic reservoir function leads to a rise in aortic reservoir pressure that is an independent predictor of cardiovascular events. Although there is evidence that high-intensity interval training (HIIT) would be useful to improve aortic reservoir pressure, the optimal dose of high-intensity exercise to improve aortic reservoir function has yet to be investigated. Therefore, this study compared the effect of different volumes of HIIT and moderate-intensity continuous training (MICT) on aortic reservoir pressure in participants with the metabolic syndrome (MetS). Methods: Fifty individuals with MetS were randomized into one of the following 16-week training programs: MICT [ n  = 17, 30 min at 60–70% peak heart rate (HRpeak), five times/week]; 4 × 4-min high-intensity interval training (4HIIT) ( n  = 15, 4 × 4 min bouts at 85–95% HRpeak, interspersed with 3 min of active recovery at 50–70% HRpeak, three times/week); and 1 × 4-min high-intensity interval training (1HIIT) ( n  = 18, 1 × 4 min bout at 85–95% HRpeak, three times/week). Aortic reservoir pressure was calculated from radial applanation tonometry. Results: Although not statistically significant, there was a trend for a small-to-medium group × time interaction effect on aortic reservoir pressure, indicating a positive adaptation following 1HIIT compared with 4HIIT and MICT [F (2, 46) = 2.9, P  = 0.07, η 2  = 0.06]. This is supported by our within-group analysis wherein only 1HIIT significantly decreased aortic reservoir pressure from pre to postintervention (pre–post: 1HIIT 33 ± 16 to 31 ± 13, P  = 0.03; MICT 29 ± 9–28 ± 8, P  = 0.78; 4HIIT 28 ± 10–30 ± 9 mmHg, P  = 0.10). Conclusion: Three sessions of 4 min of high-intensity exercise per week (12 min/week) was sufficient to improve aortic reservoir pressure, and thus may be a time-efficient exercise modality for reducing cardiovascular risk in individuals with MetS.